Translation of the English nominal suffixes into Indonesian in Louisa May Alcott’s little woman: The equivalent and shift category - Maisarah, Ira; Oktariani, Ade Suci; Erniyati, Yelni (Journal of Applied Studies in Language, 2022)
This study analyzed the category shift on the translation of nominal suffixes in English and their equivalents in Indonesian. The data are taken from the novel Little Women by Louisa May Alcott and the Indonesian version translated by Annisa Cinantya Putri. This study used a qualitative method while the category shift was analyzed using Hatim & Munday framework. The result of the research shows that there are three kinds of shift that occurred: Class-shift (the changes of word classes), Structure-shift (the initial headword in English becomes the final in Indonesian), and Unit-shift (the changes of rank). The English nominal suffixes that are found in the novel can be equivalent to Indonesian affixes (suffix, prefix, confix, affix) combination reduplication, word, and phrase.